(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
New investigations carried out on the samples which allowed Airoldi, in 1932, to establish the species Lithothamnium stefaninii, showed morphological and structural characters pointing to the attribution of the taxon to the genus Archaeolithothamnium; since Archaeolithothamnium stefaninii was preoccupied ’by Raineri in 1929, for another species, it is necessary to change the specific name of the taxon under discussion to Archaeolithothamnium airoldii.